Relationship of body weight with gastrointestinal motor and sensory function: studies in anorexia nervosa and obesity. Issue 1 (December 2017) - Bluemel, Sena; Menne, Dieter; Milos, Gabriella; Goetze, Oliver; Fried, Michael; Schwizer, Werner; Fox, Mark; Steingoetter, Andreas
Abstract Background Whether gastrointestinal motor and sensory function is primary cause or secondary effect of abnormal body weight is uncertain. Moreover, studies relating continuous postprandial sensations of satiation to measurable pathology are scarce. This work assessed postprandial gastrointestinal function and concurrent sensations of satiation across a wide range of body weight and after weight change. Methods Patients with anorexia nervosa (AN) and obesity (OB) were investigated in reference to normal weight controls (HC). AN were additionally investigated longitudinally. Gastric emptying, antral contractions and oro-cecal transit after ingestion of a solid meal were investigated by MRI and13 C-lactose-ureide breath test. The dependency of self-reported sensations of satiation on the varying degree of stomach filling during gastric emptying was compared between groups. Results 24 AN (BMI 14.4 (11.9–16.0) kg/m2 ), 16 OB (34.9 (29.6–41.5) kg/m2 ) and 20 HC (21.9 (18.9–24.9) kg/m2 ) were studied. Gastric half-emptying time (t50 ) was slower in AN than HC (p  = 0.016) and OB (p  = 0.007), and a negative association between t50 and BMI was observed between BMI 12 and 25 kg/m2 (p  = 0.007). Antral contractions and oro-cecal transit were not different. For any given gastric content volume, self-reported postprandial fullness was greater in AN than in HC or OB (p  < 0.001). After weight rehabilitation, t50 in AN tended to become shorter (p  = 0.09) and postprandial fullness was less marked (p  < 0.01). Conclusions A relationship between body weight and gastric emptying as well as self-reported feelings of satiation is present. AN have slower gastric emptying and heightened visceral perception compared to HC and OB. Longitudinal follow-up after weight rehabilitation in AN suggests these abnormalities are not a primary feature, but secondary to other factors that determine abnormal body weight. Trial registration Registered July 20, 2009 at ClinicalTrials.gov (NCT00946816 ).